TINJAUAN KELAYAKAN FASILITAS DIFABEL PADA STASIUN MASS RAPID TRANSIT HAJI NAWI JAKARTA SELATAN - Sugandi; Ayu Oktaviani (Universitas Krisnadwipayana, Fakultas Teknik Program Studi Arsitektur, 2021)
The Mass Rapid Transit (MRT) station is one of the public facilities that support activities forall groups of people. The appropriateness of public facilities in accordance with applicablestandards and regulations is something that needs to be considered in the fulfillment of publicfacilities, especially for persons with disabilities or disabilities, which of course require specialstandards. The purpose of this study is to review facilities for persons with disabilities at theHaji Nawi Mass Rapid Transit (MRT) Station, so that later it can be seen whether the facilitiesfor persons with disabilities at Haji Nawi Station are appropriate in accordance withapplicable standards. The method used in this study is a comparison method with reference tothe applicable standards. The results of this study can be concluded that the facilities forpersons with disabilities at the Haji Nawi Mass Rapid Transit (MRT) Station in several areasare not in accordance with the applicable standards, the unavailability of guiding blocks in theplatform area, taxi waiting shelters, signage in the disabled parking area. some areas that arein the service area that meet the standards